Dynamics of Dispersive Wave Generation in Gas-Filled Photonic Crystal Fiber with the Normal Dispersion. (30th August 2017) - Deng, Zhixiang; Zhang, Meng
Abstract : The absence of Raman and unique pressure-tunable dispersion is the characteristic feature of gas-filled photonic crystal fiber (PCF), and its zero dispersion points can be extended to the near-infrared by increasing gas pressure. The generation of dispersive wave (DW) in the normal group velocity dispersion (GVD) region of PCF is investigated. It is demonstrated that considering the self-steepening (SS) and introducing the chirp of the initial input pulse are two suitable means to control the DW generation. The SS enhances the relative average intensity of blue-shift DW while weakening that of red-shift DW. The required propagation distance of DW emission is markedly varied by introducing the frequency chirp. Manipulating DW generation in gas-filled PCF by the combined effects of either SS or chirp and three-order dispersion (TOD) provides a method for a concentrated transfer of energy into the targeted wavelengths.